Preparation and In Vitro Evaluation of a Simple Ointment Containing Ethanolic Extract of Turbinaria ornata, a Brown Alga from Red Sea, Jazan, KSA (Asian Journal of Pharmaceutics (AJP), 2018)
Objective: The purpose of this work is to investigate the antibacterial activity of Turbinaria ornata (Turner) J. Agardh, a rare brown alga belonging to the Sargassaceae family collected from Red Sea, Jazan, KSA. The study also focuses on the formulation of a topical ointment for healing wounds. Materials and Methods: The phytochemical extraction was performed using the Soxhlet apparatus by a hot continuous percolation technique, with ethanol as the solvent. The crude extract was analyzed to find out various phytoconstituents. The extract was screened for antibacterial potency against selected human pathogenic bacteria, namely Staphylococcus aureus, Streptococcus pyogenes, Bacillus subtilis, Klebsiella pneumonia, Escherichia coli, and Pseudomonas aeruginosa. In this study, the extract was further formulated into a 1% w/v ointment which was screened against the test bacteria. Results: The ethanol extract of T. ornata has shown the presence of carbohydrates, proteins, amino acids, alkaloids, saponin, fixed oil, fat, tannins, and flavonoids. The crude extract and ointment elicited good antibacterial effect against S. aureus, S. pyogenes, B. subtilis, and E. coli but were inactive against Kl. pneumonia and P. aeruginosa. However, the antibacterial effect was more pronounced in the ointment compared to the crude extract. Conclusion: T. ornata has shown potent antibacterial properties against selected human pathogenic bacteria. The present study may lead to new antibacterial formulations for topical applications.